2014
DOI: 10.3851/imp2958
|View full text |Cite
|
Sign up to set email alerts
|

Liver-to-Plasma Vaniprevir (MK-7009) Concentration Ratios in HCV-Infected Patients

Abstract: Background Some drugs that are actively taken up into the liver exhibit greater than dose proportional increases in plasma exposure, although human liver-to-plasma concentration ratios have rarely been evaluated. Understanding these relationships has implications for drug concentrations at the target site for certain classes of compounds, such as direct-acting antivirals, targeted towards HCV. Methods Treatment-experienced, chronic HCV non-cirrhotic patients (n=3) received vaniprevir (600 mg or 300 mg twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…In this study, we assessed rat plasma and liver concentrations of paritaprevir and ritonavir by utilizing samples obtained by tissue resection, biopsy, and fine-needle aspiration. As anticipated from previous animal studies with ritonavir and the clinical data for the protease inhibitor vaniprevir, we found that both drugs were highly concentrated within the liver compared to plasma (3,11,20). Their liver concentrations, however, differed by tissue sample type, with the highest concentrations obtained for resection samples, followed by CNB, FNA 5 , FNA 3 , and FNA 1 samples.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In this study, we assessed rat plasma and liver concentrations of paritaprevir and ritonavir by utilizing samples obtained by tissue resection, biopsy, and fine-needle aspiration. As anticipated from previous animal studies with ritonavir and the clinical data for the protease inhibitor vaniprevir, we found that both drugs were highly concentrated within the liver compared to plasma (3,11,20). Their liver concentrations, however, differed by tissue sample type, with the highest concentrations obtained for resection samples, followed by CNB, FNA 5 , FNA 3 , and FNA 1 samples.…”
Section: Discussionsupporting
confidence: 66%
“…It also permitted development of a normalization procedure to determine the percentage of liver contained within the sample through the identification of liver-enriched genes (21). As a follow-up to the initial study, we conducted two studies investigating liver-to-plasma drug concentration ratios (10,11). In the first, we performed CNB on three patients treated with vaniprevir and demonstrated higher human liver concentrations than the concentrations in plasma (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations